Implementasi Kebijakan Pengaduan Masyarakat Melalui Aplikasi WargaKu Surabaya (Studi Kasus: Dinas Komunikasi dan Informatika Kota Surabaya) - Allifiyah, Rhizma Ananda; Agus Prastyawan (Universitas Negeri Surabaya, 2023)
The Surabaya City Communication and Informatics Office created an innovation in the form of implementing e-gov for the people of Surabaya City in making complaints. This innovation is known as the WargaKu Surabaya application. The hope with this application is that it will be easier for people to submit reports easily. But the reality on the ground when implementing this application there are still obstacles, namely 1). The community reports but has the wrong objective, 2). Complaints from the community that responding to complaints reports takes a long time to respond to complaints from the public. The purpose of this research is to analyze and describe the implementation of the community complaint policy through the WargaKu Surabaya application. This type of research is descriptive qualitative. Source collection technique with purposive sampling. In this study, observation, interviews, and documentation were used as data collection methods. Informants from the Office of Communications and the community participated in this research. The data analysis technique used is data reduction, data presentation, drawing conclusions. In addition, researchers use a research focus using Policy Implementation Theory which consists of Communication indicators. Resources, Disposition or Attitude of Executors, and Bureaucratic Structure. In this study, the results of this study were obtained using George C. Edwards III Theory, in which there were categories 1) Transmission was said to be good because the policy makers and policy implementers had socialized about 7 times before the new policy regarding public complaints, 2) Good clarity because the socialization regarding the formulation of policy implementation which was attended by the Head of Service, Electronic / e-gov Based Government Services, and the Complaint Service to socialize the formulation of the policy for implementing the Surabaya WargaKu Complaint Application was quite clear because the directions and language used were easy to understand and understood by policy implementers., 3) Consistency is not good because the policy formulator for the head of the service is not consistent in conducting outreach to policy implementers, this reason is because the policy formulator (kadin) is too busy taking care of other work at the Surabaya City Communication and Informatics Office. Keywords: Electronic Government, Policy Implementation, Wargaku Surabaya